EVALUATION OF PHARMACY MANAGEMENT INFORMATION SYSTEM IMPLEMENTATION BASED ON USER PERCEPTION IN IMMANUEL HOSPITAL BANDUNG - Randy Tampa'i; Satibi Satibi; Gunawan Pamudji (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Technology and information systems can help an organization to execute various activities accurately, punctually and in good quality, so that can increase the efficiency, effectivenesss and competitiveness of the organization. Success in implementing information systems can be determined by an evaluation of information systems that have been applied. The purpose of this study was to evaluate the application of information systems that have been implemented at Immanuel Hospital Bandung, using information systems success models developed by DeLone and McLean. This study was a descriptive study using cross sectional design. Data was obtained from questionnaire to employees and in depth interview to Director of Hospital, Head of Pharmacy Departement and Head of Technology and Information system departement. The research examined variable is user satisfaction to the accuracy, completeness, relevance, timeliness, auditability, and the reliability of pharmacy management information system at Immanuel Bandung Hospital. The data which have been collected from questionnaires then analyzed using qualitative analysis. The results of the study showed that the user satisfaction management information system in Immanuel Bandung Hospital were in medium category. The average user satisfaction ranges between 2.50 to 3.33 of 5 scales. The highest level of user satisfaction of information systems management was on timeliness aspects, auditability, accuracy and completeness. Relevance and reliability had the lowest satisfaction.Keywords : evaluation, pharmacy management information system, user perceptions.